Β2‐Adrenergic Receptor Activation by Agonists Studied with 19F NMR Spectroscopy1. Issue 41 (16th August 2013) - Horst, Reto; Liu, Jeffrey J.; Stevens, Raymond C.; Wüthrich, Kurt
<x xml:space="preserve">Abstract</x> Proteins in slow motion: 19F NMR studies indicate that equilibria between active and inactive states of the human β2‐adrenergic receptor require extensive structural rearrangements (arrows in picture). This was shown by an enthalpy difference of ΔHo≈40 kJ mol−1 and a slow exchange rate, with kex≪10 s−1.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>